The Development of Inner Tourism: Problems and Prospects under the Modern Russian Conditions - FROLOVA, Elena Victorovna; KABANOVA, Elena Evgen'evna; MEDVEDEVA, Natalia Vladimirovna (Journal of Environmental Management and Tourism, 2016)
The article is devoted to the current economic problem-the development of inner tourism. The peculiarities and the development of problems relating to the tourism in the Russian Federation have been determined on the basis of statistical and sociological information. In this article we provided the analysis of the Russian and international experience, determined the most fruitful mechanisms on developing touristic attractiveness of these territories which may be adapted and demanded under the current conditions. As international experience showed the development based on the scientific research significantly stipulated the increase of touristic flow. The investigations should be aimed at revealing the parameters of perception concerning specific peculiarities at the determined territory, local culture, traditions, the analysis of the requirements of would-be consumers, the determination of priorities in the realization of the touristic initiatives, the assessment of effectiveness of tourism development at the determined territory. Both: international and Russian experience show that it is necessary to revive, maintain, and develop unique peculiarities of a territory, local culture, traditions and customs that should also involve activity of inhabitants. It is significant that exactly local creative groups participate in the development of inner tourism. The analysis showed that it is exactly the consolidation of efforts put in by the local authorities, business, and inhabitants at the local level that is considered to be the most fruitful management practice in making inner tourism attractive at that or another territory. The most effective directions of management activity include the following aspects: the creation and development of unique objects of touristic attractiveness, the actualization of cultural and historic inheritance, search for innovative ideas in developing event tourism and their realization, modernization of practice concerning touristic products and services in the field of folklore, folk craft, and local initiatives.
Keywords: inner tourism; tourism attractiveness; techniques of development of touristic attractiveness; strategic partnership; management practices